2001
DOI: 10.1097/00007890-200110150-00011
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF SIROLIMUS ON THE METABOLISM OF ApoB100- CONTAINING LIPOPROTEINS IN RENAL TRANSPLANT PATIENTS1

Abstract: This study indicates that for renal transplant patients in whom RAPA treatment induces hyperlipidemia, this effect is the result of reduced catabolism of apoB100-containing lipoproteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
62
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(65 citation statements)
references
References 24 publications
3
62
0
Order By: Relevance
“…In that study, treatment with sirolimus was associated with a 70% decrease in VLDL-apoB100 catabolism and a 28% decrease in IDL-apoB100 catabolism (56). In line with these kinetic results, a significant decrease in post-heparin lipoprotein lipase (LPL) activity (the major enzyme responsible for triglyceride catabolism) was observed in patients showing sirolimus-induced hypertriglyceridemia (56) (Fig. 2).…”
Section: Effects Of Mtor Inhibitors On Lipids "supporting
confidence: 59%
See 4 more Smart Citations
“…In that study, treatment with sirolimus was associated with a 70% decrease in VLDL-apoB100 catabolism and a 28% decrease in IDL-apoB100 catabolism (56). In line with these kinetic results, a significant decrease in post-heparin lipoprotein lipase (LPL) activity (the major enzyme responsible for triglyceride catabolism) was observed in patients showing sirolimus-induced hypertriglyceridemia (56) (Fig. 2).…”
Section: Effects Of Mtor Inhibitors On Lipids "supporting
confidence: 59%
“…It has been postulated that this increase in free fatty acids may increase hepatic VLDL production, but such increase in VLDL production has not been clearly shown in human kinetic studies (56). As far as LDL cholesterol is concerned, a kinetic study performed in renal transplant patients has shown that treatment with sirolimus was associated with a 68% decrease in LDL-apoB100 catabolism (56). It has been shown in vitro with HepG2 cells that sirolimus reduced LDL receptor (LDLr) expression leading to diminished LDL uptake (58) (Fig.…”
Section: Effects Of Mtor Inhibitors On Lipids "mentioning
confidence: 98%
See 3 more Smart Citations